Factors influencing job satisfaction in the Malaysian Vocational College: herzberg two factor theory perspective - Mustafa, Mohamad Zaid; Yamin, Noor Azlin; Abdul Razzaq, Abdul Rasid; Ahad, Rosnee (HRPUB, 2022)
Teaching nowadays requires high commitment from teachers; the workload is heavy, the role is broad and the teachers are directly responsible for educating and developing the students. Educating and developing technical and vocational students requires quality, competent and high commitment teachers. Without commitment and motivation, they feel dissatisfied, or lack of passion in their job and the worst situation, some of them may withdraw or turnover from the profession. Teachers will achieve job satisfaction when the motivation and hygiene factors complement each other. Vocational colleges want their teachers to have the best possible performance. However, how to motivate the teachers? There is not much point in motivating them if they do not care about hygiene factors. Motivating people to work when the things they complain about disappear. When the dissatisfaction is taken away, the institutions can focus on motivating teachers effectively. Hence, the purpose of this study is to highlight the factors that affect job satisfaction in vocational colleges in Malaysia and identify the factors that affect job satisfaction. This study used Two-Factor Theory from Herzberg to decide how significant hygiene and motivator factors are related to job satisfaction among the vocational teachers and how the two factors complement each other. Among the factors identified are company policy, supervision, work conditions, salary, recognition, the work itself, personal growth, and achievement. This study also has theoretical implications for directing future developments study and offers practical suggestions to the management in the improvement of job satisfaction among vocational teachers. Job satisfaction is essential for individuals and vocational colleges. Factors affecting job satisfaction need to be given more attention to improve the quality of education and thus achieve student success. Herzberg Two-Factor Theory provides two factors that affect teachers' motivation in the workplace. Hygiene factors will influence teachers’ working less if they are not present, while motivational factors will motivate teachers to work better if they are present. Therefore, any hygiene factors must be resolved first, and then motivating factors must be boosted.